Sifat-Sifat Biokimiawi dan Fabrikasi Ganoderma Jamur Patogen Pohonan - Agus Susanto (Universitas Gadjah Mada, 1998)
Besides as a cause of tree disease, Ganoderma is also a medicine for human health. Ganoderma used as medicine is Ganoderma lucidum. This fungus contains polysaccharides, terpenoid, ganoderic acid, germanium, protein, adenosine, and fiber. All of these materials have the following properties: antitumor activities, increase of oxygen in brain, balance of bioelectric function, decrease of cholesterol and glucose concentration in blood, detoxification of poison, etc. because of that, Ganoderma is used to cure diabetes, stroke, hypertension, and it is used as a tonic to promote good health in old age.